2000
DOI: 10.1001/archneur.57.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil Therapy in Clinical Practice

Abstract: This independent confirmation of data from phase 3 trials suggests that donepezil therapy modestly improves cognition in patients with Alzheimer disease who are encountered in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(104 citation statements)
references
References 21 publications
5
97
1
1
Order By: Relevance
“…Early reports in relatively small cohorts with AD suggested that the AChE inhibitors tacrine 23 and donepezil 24 showed increased efficacy in APOE e4-negative or -positive patients, respectively. However, studies in larger AD cohorts have not replicated these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports in relatively small cohorts with AD suggested that the AChE inhibitors tacrine 23 and donepezil 24 showed increased efficacy in APOE e4-negative or -positive patients, respectively. However, studies in larger AD cohorts have not replicated these findings.…”
Section: Discussionmentioning
confidence: 99%
“…20 The majority of drug trials have used the ADAS-Cog 15,[21][22][23][24] to measure cognitive function, although many studies have also continued to use the ubiquitous MMSE. 25 For global change, most trials have used the CIBICplus.…”
Section: Evaluating Treatmentmentioning
confidence: 99%
“…Eight published RCTs were parallel comparisons of donepezil with placebo, 41,[43][44][45][46][47][48][49] three RCTs compared two doses of donepezil with placebo, [50][51][52] one compared three doses of donepezil with placebo 53 and one was a crossover comparison of donepezil with placebo. 54 One unpublished RCT reports data on participants with mild AD. 55 In four of the eight trials with a two-arm comparison, the dose of donepezil was 5 mg/day for 28 days followed by 10 mg/day for the remainder of the study duration, 41,[45][46][47] and in another the dose of donepezil was 5 mg/day for 42 days followed by 10 mg/day for the remainder of the study duration.…”
Section: Donepezil Quantity and Quality Of Researchmentioning
confidence: 99%